Asian discourses of rule of law : theories and implementation of rule of law in twelve Asian countries, France and the U.S. - Peerenboom, R. P. (Randall P.), 1958- (London ; New York : RoutledgeCurzon, 2004)
Rule of law, one of the pillars of the modern world, has emerged in Western liberal democracies. This book considers how rule of law is viewed and implemented in the different cultural, economic and political context of Asia.
Varieties of rule of law: an introduction and provisional conclusion / Randall Peerenboom -- Rule of law in the United States / Brian Z. Tamanaha -- Rule of law in France / Laurent Pech -- Competing conceptions of rule of law in China / Randall Peerenboom -- Concept of law in Vietnam: transforming statist socialism / John Gillespie -- Rule of law within a nonliberal "communitarian" democracy: the Singapore experience / Li-Ann Thio -- Competing conceptions of rule of law in Malaysia / H.P. Lee -- Debating rule of law in the Hong Kong Special Administrative Region, 1997-2002 / Albert H.Y. Chen and Anne S.Y. Cheung -- Indonesia: devaluing Asian values, rewriting rule of law / Tim Lindsey -- Rule of law in India: theory and practice / Upendra Baxi -- Rule of law and aspects of human rights in Thailand: from conceptualization to implementation? / Vitat Muntarbhorn -- The Philippine "People Power" constitution, rule of law, and the limits of liberal constitutionalism / Raul C. Pangalangan -- Rule of law in South Korea: rhetoric and implementation / Hahm Chaihark -- The effects of rule of law principles in Taiwan / Sean Cooney -- Rule of law in Japan / John O. Haley and Veronica Taylor.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Rule of law -- Asia; Rule of law -- France; Rule of law -- United States; Règle de droit -- Asie; Règle de droit -- France; Règle de droit -- États-Unis.; LAW -- Jurisprudence; LAW -- General Practice; LAW -- Reference; LAW -- Essays; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; Rule of law; Asia; France; United States